ChemInform Abstract: Conformational Analysis of Furanoside‐Containing Mono‐ and Oligosaccharides. Issue 17 (4th April 2013) - Taha, Hashem A.; Richards, Michele R.; Lowary, Todd L.
Abstract Review: 564 refs.